How green is your packaging—A comparative international study of cues consumers use to recognize environmentally friendly packaging. (13th January 2020) - Herbes, Carsten; Beuthner, Christoph; Ramme, Iris
Abstract: Consumers have grown increasingly aware of the impact of packaging on the environment. Therefore, interest has grown in more environmentally friendly packaging, but we wondered how consumers recognize 'green' as distinct from 'grey' when evaluating packaging. We asked over 3, 000 respondents from Germany, France and the United States how they recognize environmentally friendly packaging. To solicit responses that we may not have anticipated, we used an open‐ended format, which we then followed with a closed‐ended format so that we could compare the two sets of responses. Not surprisingly, in both sets of responses, we found labelling to be the attribute consumers rely upon most, as well as evidence of misleading labels. We also found consumers in Germany and the United States relied on information on the packaging and named searching for information as one of their preferred ways to decide whether packaging is environmentally friendly. French consumers seemed less trusting of published information and more trusting of the look and feel, especially the material, of the package. Our results point to the importance of cultural influences in the acquisition of perceptual cues by the consumer.